Thar she bursts - Reducing confusion reduces bubbles - Michael Kirchler; Jürgen Huber; Thomas Stöckl (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2011)
To explore why bubbles frequently emerge in the experimental asset market model of Smith, Suchanek and Williams (1988), we vary the fundamental value process (constant or declining) and the cash-to-asset value-ratio (constant or increasing). We observe high mispricing in treatments with a declining fundamental value, while overvaluation emerges when coupled with an increasing C/A-ratio. A questionnaire reveals that the declining fundamental value process confuses subjects, as they expect the fundamental value to stay constant.Running the experiment with a different context (stocks of a depletable gold mine instead of stocks) significantly reduces mispricing and overvaluation as it reduces confusion.
Keywords: C91; D03; 330; Experimental economics; asset market; bubble; market efficiency; confusion; Experimentelle Ökonomik; Bubbles; Anlageverhalten; Markteffizienz; Theorie